2021
DOI: 10.1002/slct.202004321
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Proton in the Formation of Particles: Soap‐free Emulsion Polymerization of Styrene using AIBN and Potassium Persulfate as Initiators

Abstract: In this paper, the hydrophobic effect or hydration of hydrophobe was firstly introduced into the mechanism of polystyrene particles formation. Negatively charged surface of hydration shell was proposed due to the ordered structure of water molecules. Consequentially the concentration of hydrophobic chains depended on pH because protons destroyed the hydration shell, thereby extruded hydrophobic chains from the H-bonds networks. The soap-free emulsion polymerization of styrene by using AIBN (azodiisobutyronitri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 59 publications
(113 reference statements)
2
16
1
Order By: Relevance
“…Here, it should be remarked that the deposited PSt quickly re-dissolved soon after DC was deposed. This result is the basis that we postulated the theory of hydration cage incurring entropic charge in the previous paper [35] and alcoholization cage incurring entropic charge that will be discussed in this paper.…”
Section: Preliminary Experiments: Phase-separation Of St In Ethanol and Electricity Of Pstsupporting
confidence: 56%
See 4 more Smart Citations
“…Here, it should be remarked that the deposited PSt quickly re-dissolved soon after DC was deposed. This result is the basis that we postulated the theory of hydration cage incurring entropic charge in the previous paper [35] and alcoholization cage incurring entropic charge that will be discussed in this paper.…”
Section: Preliminary Experiments: Phase-separation Of St In Ethanol and Electricity Of Pstsupporting
confidence: 56%
“…However, the percentage of low MW portion was about 8.7 %, much smaller than ∼ 30 % in water (Table 2), and also the number-averaged molecular weight was 32,750, larger than 24,100 in water. As we discussed in the previous paper, [35] the smaller MW (1,500-300) was ascribed to the high concentration of AIBN in the monomer phase. Hence, these results indicated that the concentration of AIBN in the monomer phase was 2, aside the shape of GPC diagrams and the smaller MW in MeOH, EtOH and IPA, the main MW was ∼ 4,400, ∼ 5,000 and ∼ 6,600, which were much smaller than MWs (∼ 24,000 to 33,000) in water and EG, respectively.…”
Section: Effects Of Alcohol Polarity On the Formation Of Microspheres Of Styrenementioning
confidence: 56%
See 3 more Smart Citations